2015
DOI: 10.3389/fnins.2015.00461
|View full text |Cite
|
Sign up to set email alerts
|

How Can Music Influence the Autonomic Nervous System Response in Patients with Severe Disorder of Consciousness?

Abstract: Activations to pleasant and unpleasant musical stimuli were observed within an extensive neuronal network and different brain structures, as well as in the processing of the syntactic and semantic aspects of the music. Previous studies evidenced a correlation between autonomic activity and emotion evoked by music listening in patients with Disorders of Consciousness (DoC). In this study, we analyzed retrospectively the autonomic response to musical stimuli by mean of normalized units of Low Frequency (nuLF) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 85 publications
(99 reference statements)
1
37
0
1
Order By: Relevance
“…Indices of SampEn and FuzzyMEn, as the reflections of nonlinear dynamic characteristics, could evaluate the inherent complexities of RRI time series under different emotional states [20][21][22]. Riganello et al reported that there was a significant difference in SampEn between the healthy subjects and vegetative state/unresponsive wakefulness syndrome (US/UWS) patients when listening to the Mussorgsky's music [25]. We found that there was a significant decrease in FuzzyMEn during happiness emotion, confirming the complexity of RRI time series for happiness emotion decreased.…”
Section: Effects Of Hr and Map On Hrv Indicesmentioning
confidence: 99%
“…Indices of SampEn and FuzzyMEn, as the reflections of nonlinear dynamic characteristics, could evaluate the inherent complexities of RRI time series under different emotional states [20][21][22]. Riganello et al reported that there was a significant difference in SampEn between the healthy subjects and vegetative state/unresponsive wakefulness syndrome (US/UWS) patients when listening to the Mussorgsky's music [25]. We found that there was a significant decrease in FuzzyMEn during happiness emotion, confirming the complexity of RRI time series for happiness emotion decreased.…”
Section: Effects Of Hr and Map On Hrv Indicesmentioning
confidence: 99%
“…Listening to music is usually a very pleasurable experience for the humans (Dube and Le Bel 2003). Music can be defined as an organization of the tones over the time with a strong impact on the allostatic regulatory mechanisms including autonomic nervous system (ANS) (Riganello et al 2015). Several studies showed a correlation between listening to music, noise or pure sounds and activity of cardiac autonomic regulation (Perez-Lloret et al 2014, Orini et al 2010, Iwanaga et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…22 Different smell, music, vestibular mobilization, modulated color light can influence the autonomic nervous system which leads to improved consciousness. [23][24][25][26][27][28] In this study, appropriate sensory stimuli, purposeful movement and repetition composnents of Rood's approach was employed in stimulating the cortical area and development of motor skill. According to earlier studies, somato sensory input to the motor cortex normally plays a vital role in learning new motor skills and takes a crucial part in motor relearning after stroke hemiplegia.…”
Section: Introductionmentioning
confidence: 99%